Inovasi Pembelajaran Literasi: Strategi Efektif untuk Meningkatkan Pemahaman Membaca di Sekolah Dasar - Afandi, Abdar Azmi; Sholehah, Amillah; Hasanah, Kamilatul; Mas’odi, Mas’odi (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper focuses on examining and analyzing effective strategies that teachers can implement to improve students' reading literacy skills at the primary school level. Reading literacy is seen as a fundamental skill that does not only include the ability to read and write. Rather, it involves critical comprehension, evaluation of information, and application of knowledge in the context of everyday life. The research method applied in this study is a literature study and descriptive analysis of various relevant sources. The results of the analysis show that there are various strategies that have the potential to improve students' reading literacy. Strategies include the utilization of varied learning methods, project-based learning approaches, integration of information technology, and the development of reading interest through the establishment of a supportive learning environment.